Genetic changes of non-small cell lung cancer under neoadjuvant therapy - Warth, Arne; Endris, Volker; Stenzinger, Albrecht; Penzel, Roland; Harms, Alexander; Abdollahi, Amir; Schirmacher, Peter; Muley, Thomas; Dienemann, Hendrik; Pfarr, Nicole; Weichert, Wilko (OncoTarget, 2016)
Oncotarget | https://doi.org/10.18632/oncotarget.8858 Arne Warth, Volker Endris, Albrecht Stenzinger, Roland Penzel, Alexander Harms, Thomas Duell, Amir Abdollahi, Michael Lindner, Peter Schirmacher, Thomas...